Coppinsiella extremiorientalis I. V. Frolov, Yakovczenko & A. Ezhkin 2022, spec. nov. - Frolov, Ivan V.; Prokopiev, Ilya A.; Yakovchenko, Lidia S.; Galanina, Irina A.; Ezhkin, Alexander K. (Zenodo, 2022)
Coppinsiella extremiorientalis I. V. Frolov, Yakovczenko & A. Ezhkin, spec. nov. MycoBank no. 842595 Thallus epiphytic, thin to disappearing, white or whitish grey, rarely with low amounts of anthraquinones, greenish yellow. Vegetative diaspores absent. Apothecia ca. 0.5–0.6 mm diam., zeorine; disc and true exciple dull orange with white pruina; thalline exciple usually with yellow tinge, persistent, but often present only on the lower side of apothecia. Ascospores 10–15 × 5–8 μm, with septa 3–5 μm wide. Anthraquinones composition corresponding to chemosyndrome A. Type:— RUSSIA. Sakhalin Region: Sakhalin Island, Tymovskoe District, E outskirts of Ado-Tymovo, near bridge over Pilenga river, broad floodplain between rivers Pilenga and Tym’, elev. 40 m, 51°7’56.703”N, 142°41’18.139”E, on bark of Chosenia arbutifolia in low-density forest with large trees of Populus suaveolens s. lat. and Salix spp. and high dense thickets of ferns, Urtica sp., Petasites amplus etc., 9 July 2019, I. V. Frolov 2332 (holotype LE L–17109, isotypes H, PRA, hb. Frolov). GenBank Accession numbers of the sequences of the holotype: OM 337875 (nrITS), OM 337873 (mrSSU). (Fig. 2) Thallus epiphytic, usually poorly developed or even disappearing, continuous or rimose to rimose-areolate with areoles about 0.3 × 0.2 mm and usually uneven surface, irregular in outline, up to ca. 2 cm diam. or, when several thalli merge, forming patches more than 10 cm in length that extend along the bark, white to whitish grey, rarely greenish yellow; thickness of thallus (75–)85–102–122(–175) μm [20; 4; 26]. Cortex on section colourless to grey, alveolate, but usually vivid cells 4–9 μm diam. only distinguishable in thin lower part of cortex; crystals of different form about 1–7 μm size insoluble in K fil cortex section and cover cortex surface; thickness of cortex together with epinecral layer (15–)22–25–28(–38) μm [20; 4; 6]. Algal layer (38–)52–62–67(–100) μm thick [20; 4; 18]; algal cells globose, (7.0–)11.2–12.0–12.9(–19.0) μm diam. [30; 3; 2.4]. Medulla ...